Gastroesophageal Reflux in Children : GER in Children - Vandenplas, Yvan (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of Gastroesophageal reflux (GER) in children, discussing its epidemiology, pathophysiology diagnosis and treatments. Readers will discover diverse perspectives of the contributing authors and extensive discussions of issues including GER in special patient populations and current approaches to GER diagnosis and management. The first part of the book is dedicated to introducing the condition, discussing epidemiology, symptoms and diagnosis. This is followed by addressing issues of the condition encountered in special patient populations such as in preterm infants, apnea, neulorogic patients and cystic fibrosis, among others. The final part of the book is dedicated to therapeutic approaches from meditation to surgery and alternative approaches such as complementary medicine and hypnotherapy. The approaches and challenges in endoscopy are discussed in a final chapter. Edited by a leading world expert in the topic and written by a global team of authors, this book will appeal to a wide readership from pediatricians, gastroenterologists to pulmonologists, otolaryngologists and neurologists. For the first time, information on GER in patients 0--15 years is brought together in one volume, discussing all the key issues that for experts.